2021 IFPRI A-133 (Uniform guide) - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
We have audited the accompanying financial statements of International Food Policy Research Institute (IFPRI), which comprise the statements of financial position as of December 31, 2021 and 2020, the related statements of activities, functional expenses, changes in net assets and cash flows for the years then ended and the related notes to the financial statements.